Changes in HIV Testing Utilization Among Chinese Men Who Have Sex With Men During the COVID-19 Pandemic in Shenzhen, China: An Observational Prospective Cohort Study - Zhang, Kechun; Chen, Siyu; Chan, Paul Shing-fong; Fang, Yuan; Cao, He; Chen, Hongbiao; Hu, Tian; Chen, Yaqi; Zhou, Xiaofeng; Wang, Zixin (Frontiers in Medicine, 2022)
Background: The Coronavirus Diseases 2019 (COVID-19) directly affects HIV prevention and sexual health services utilization among men who have sex with men (MSM). This study investigated changes in human immunodeficiency virus (HIV) testing utilization among MSM before and after the COVID-19 pandemic received initial control in Shenzhen, China. Methods: This study was a sub-analysis of a prospective observational cohort study conducted among MSM in Shenzhen, China between August 2020 and May 2021. Participants were recruited through outreaching in gay venues, online recruitment, and peer referral. Participants completed a baseline online survey between August and September 2020 and a follow-up online survey between April and May 2021. This study was based on 412 MSM who reported to be HIV-negative/unknown sero-status at baseline, 297 (72.1%) of them completed the follow-up online survey. Multilevel logistic regression models (level 1: sources of recruitment; level 2: individual participants) were fitted. Results: When comparing follow-up data with baseline data, a significant increase was observed in the uptake of any type of HIV testing (77.9% at Month 6 versus 59.2% at baseline, p<0.001). After adjusting for age group, education level, current employment status and monthly personal income, two predisposing factors were associated with higher uptake of HIV testing during the follow-up period. They were: 1) condomless anal intercourse with male non-regular male sex partners at follow-up only (AOR: 5.29, 95%CI: 1.27, 22.01) and 2) sanitizing before and after sex at baseline (AOR: 1.26, 95%CI: 1.02, 1.47). Regarding enabling factors, utilization of HIV testing (AOR: 3.90, 95%CI: 2.27, 6.69) and STI testing (AOR: 2.43, 95%CI: 1.20, 4.93) six months prior to the baseline survey was associated with higher uptake of HIV testing during the follow-up period. Having the experience that HIV testing service providers reduced service hours during the follow-up period was also positively associated with the dependent variable (AOR: 3.45, 95%CI: 1.26, 9.41). Conclusions: HIV testing utilization among MSM might rebound to the level before the COVID-19 outbreak after the pandemic received initial control in China. This study offered a comprehensive overview to identify potential reasons that can influence the uptake of HIV testing among Chinese MSM.